Demand driven supply chain a structured and practical roadmap to increase profitability - Mendes, Paulo; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This book aims to identify and describe the practical key components of demand driven supply chains, and based on these components, develops a structured and integrated assessment framework that companies can use to assess their current and desired future supply chain states in light of the Demand Driven Supply Chain (DDSC) concepts. Another contribution of the book is the structured framework developed to design a supply chain strategy, which will consider the DDSC assessment results as one of the key inputs, and will support the implementation of the opportunities identified during the assessment. The framework presented in this book was applied in different supply chain operations of a global CPG company to validate the methodology and formalize an action plan to allow these operations move towards a DDSC. Results show clear opportunities to improve supply chain operation and become more demand driven.
1. Introduction -- 2. Literature review on demand driven supply chain (DDSC) -- 3. Proposed framework -- 4. Key components of demand driven supply chain -- 5. Proposed demand driven supply chain model -- 6. Analytic hierachy process -- 7. Example of case implementation and author's DDSC website -- 8. Summary and future developments.
Electronic reproduction.
Keywords: Business logistics; Inventory control; Electronic books